Nutritional management of yellowing in arecanut - Jacob D (Department of Agronomy, College of Horticulture, 2007)
Yellowing of arecanut is the most serious problem affecting arecanut cultivation. The incidence of yellowing is noticed in isolated patches without any definite pattern. The diagnostic symptoms first appear as yellowing of leaflets in two to three leaves of outermost whorl, with abrupt demarcation between yellow and green regions. Yield in affected palms gets reduced by 30-40 per cent every year and in 3-4 years the entire garden becomes most uneconomical when left without proper management.